Effect of heat treatment on optical, elastic and thermal properties of silica borotellurite glass doped with manganese - Ismail, Zaitizila (2019)
The properties and applications of various glass materials have been improving in daily life. Rice husk is the major source of biomass waste and offer an immense potential to create bioenergy. Rice husk have been used as a source of silica in this research. In order to unveil the effect of heat treatment and manganese on physical, structural, optical, elastic and thermal properties of silica borotellurite glass system, the quaternary glass system {[(TeO2)0.7(B2O3)0.3]0.8(SiO2)0.2}1-x(MnO2)x where x = 0.00, 0.01, 0.02, 0.03, 0.04 and 0.05 molar fraction were successfully fabricated through melt quenching technique. The physical, structural, optical, elastic, and thermal properties of the glass samples were investigated by using densimeter, X-ray Diffraction (XRD) spectrometer, Fourier Transform Infrared Spectrometer (FTIR), ultrasound technique and UV-Visible Spectrophotometer (UV-VIS) as well as Differential Scanning Calorimetry (DSC). The samples underwent heat treatment process at temperature of 250 ℃, 350 ℃, 450 ℃ and 600 ℃ for 3 hours. The density of the glass is found to decrease for samples before and after heat treatment as more dopant were added into the glass system which suggest the substitution of a heavier element in the glass system by a lighter dopant. Meanwhile, the molar volume of fabricated glass increases as the concentration of manganese increase due to the growth of free volume in the glass network. The minimum and maximum values for molar volume are 2.823 x 10-5 and 3.141 x 10-5 m3/mol respectively. Structural unit of TeO4, TeO3, BO4 and BO3 were detected in samples before and after heat treatment procedure while Mn structural unit was only found in samples after heat treatment process at 600 ℃. The detection of Mn structural unit indicates that heat treatment procedure causes the glass network start to restructure. The amorphous and crystalline nature of the glass is confirmed by using XRD analysis. SEM images show the agglomeration of the particle after heat treatment process. In terms of optical band gap, refractive index, and Urbach energy, all of the samples possess the same trends as well as some variations in the values as more dopants are added into silica borotellurite glass system. The inconsistent values as well as trends for the investigated parameter suggest that the formation of bridging and non-bridging oxygen take place in the glass system. The largest value of refractive index is 3.57 while the smallest Urbach energy value among all the synthesized samples is 0.39 eV. The current value of refractive index in the market is 1.98. The small Urbach energy hints the less disorderness in the glass structure. On the other hand, the elastic moduli and other elastic parameters of the prepared glass samples are found to be inconsistent with the addition of more manganese element in the silica borotellurite glass system. The decreasing trends in the ultrasonic velocities have contributed to the decrement in rigidity and compactness of the glass system. The value of Poisson’s ratio indicated that the glass sample have high cross-link density since the values lie on the range 0.1 to 0.2 for glass samples before and after heat treatment glass samples. Furthermore, the thermal properties of the glasses show that the glass sample have increasing thermal stability and glass transition temperature with the introduction of manganese in the silica borotellurite glass system. The increment in both thermal stability as well as glass transition temperature after the addition of manganese proved that the introduces dopant increased the rigidity and the stiffness of the bond in the glass network. The prepared glass samples can be categorized as strong glass former since the fragility index for samples before and after heat treatment lies in the range of 0.84 to 0.90. In conclusion, the addition of manganese and the heat treatment process done on the silica borotellurite glass have altered the properties of the glasses in different ways. This research is able to provide new knowledge regarding transition metal doped silica borotellurite glass and effect of heat treatment on the glass system. The results from the refractive index suggests that silica borotellurite glass doped with manganese have potential to be used as UV absorbance glass.